Cavernous sinus thrombophlebitis in children - Anannit Visudtibhan (2018)
Eight Thai patients less than 15 years of age who were diagnosed with cavernous sinus thrombophlebitis at Ramathibodi Hospital, Bangkok, Thailand over the past 30 years were reviewed retrospectively. The predisposing infections and causative microorganisms were similar to previous reports in children and adults. Despite severe neurologic dysfunction during admission, including blindness, there was neither death nor severe permanent deficit found in the majority of the patients. Only one patient experienced mild hemiparesis caused by cerebral infarction, which was secondary to this condition. Early recognition of this condition, the appropriate selection of empirical antibiotic therapy, and the awareness of associated complication were the key factors leading to excellent outcome. Copyright © 2001 Elsevier Science Inc.